Development of fast response freezing valve for liquid lithium application in tokamak. (May 2016) - Chen, Zhaoxi; Yang, Qingxi; Song, Yuntao; Hu, Jiansheng; Zuo, Guizhong; Ren, Jun; Meng, Xiancai; Xu, Hao; Xu, Wei
Abstract: Liquid lithium has bright prospect for plasma facing material and coolant application in fusion experimental devices. To improve the safety performance of liquid lithium system, valve is necessary to be applied in the circuit and will be installed in the vacuum vessel. A compact structure of freezing valve, which can be operated under high vacuum, high magnetic field and high temperature (180 °C–320 °C) was designed and manufactured. The cooling performances of the freezing valve under different cooling water velocities were simulated and according to the simulation results, its response time under 2 m/s cooling water was about 3 s. The performances of the freezing valve like freezing time, thermal affected area and heating capability were tested on the test bench. Based on the experiment results, the response time was about 5 s. The thermal affected area was very limited and the heating capability of the heater was enough for the freezing valve normal operation. Through preliminary thermal shock test, the thermal fatigue resistance of the brazing joints was tested and the joints were characterized by metallographic experiment, which indicated that the structure of the valve was stable under 25 times of thermal shock tests. Highlights: Applying freezing valve in tokamak liquid lithium circuit is essential. Through R&D, the fast response freezing valve was developed successfully. The freezing valve can stand 25 cycles of thermal shock load without leaking.